2020
DOI: 10.1186/s12920-020-0692-3
|View full text |Cite
|
Sign up to set email alerts
|

Master and servant: LINC00152 – a STAT3-induced long noncoding RNA regulates STAT3 in a positive feedback in human multiple myeloma

Abstract: Background: The survival of INA-6 human multiple myeloma cells is strictly dependent upon the Interleukin-6activated transcription factor STAT3. Although transcriptional analyses have revealed many genes regulated by STAT3, to date no protein-coding STAT3 target gene is known to mediate survival in INA-6 cells. Therefore, the aim here was to identify and analyze non-protein-coding STAT3 target genes. In addition to the oncogenic microRNA-21, we previously described five long noncoding RNAs (lncRNAs) induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In previous studies we observed in Multiple Myeloma a positive feedback between LINC00152 and the transcription factor STAT3 at the transcriptional level. STAT3 induced the expression of LINC00152 lncRNA and vice versa LINC00152 raised the expression of STAT3 mRNA by a physical interaction with the STAT3 pre-mRNA 14 . To test whether such a positive feedback circle also exists in GBM cells, we performed knockdown experiments targeting STAT3 and LINC00152 by siRNAs.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In previous studies we observed in Multiple Myeloma a positive feedback between LINC00152 and the transcription factor STAT3 at the transcriptional level. STAT3 induced the expression of LINC00152 lncRNA and vice versa LINC00152 raised the expression of STAT3 mRNA by a physical interaction with the STAT3 pre-mRNA 14 . To test whether such a positive feedback circle also exists in GBM cells, we performed knockdown experiments targeting STAT3 and LINC00152 by siRNAs.…”
Section: Resultsmentioning
confidence: 96%
“…Initially we aimed to determine whether the knockdown of LINC00152 in glioblastoma (GBM) results in the same anti-tumor phenotype as it has been observed in myeloma cells 14 . Since LINC00152 was also found to be overexpressed in GBM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of miR-451a, LINC00657 and AC084082.3 are shown to interact with miR-451a in BM ( 36 ). In MM, IL-6, a vital growth factor for myeloma cells, can induce the upregulation of several lncRNAs ( 37 ), and these lncRNAs may cause miR-451a dysregulation. However, which lncRNA can sponge miR-451a in MM remains unknown.…”
Section: Discussionmentioning
confidence: 99%